Sociability, golf courses, and the performance of institutional investors - WEI, Chi Shen (Institutional Knowledge at Singapore Management University, 2016)
We hypothesize that prestigious golf courses attract golfers and visitors from across the country, providing greater opportunities for nearby investors to build social connections. Our evidence suggests that institutional investors located near prestigious golf courses earn significantly better benchmark- and risk-adjusted returns. This reflects the benefits of sociability as our findings are stronger for golf courses with reciprocal guest policies that allow wider participation and increase when major golf championships rotate to the state. Their portfolios reveal hallmarks of active trading – higher concentration, greater selectivity, more frequent turnover – and include more distant stocks. To establish a causal link, we exploit the fact that golf is a weather-dependent outdoor activity. We find that their outperformance occurs during times of low precipitation around golf courses, evaporating when bad weather keeps golfers off the greens.